2018
DOI: 10.1186/s12889-018-5247-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and long-term disease burden of herpes zoster and postherpetic neuralgia in Taiwan: a population-based, propensity score-matched cohort study

Abstract: BackgroundThe objectives of this study were to characterize the burden of herpes zoster, as well as the longitudinal and incremental changes of healthcare service utilization among individuals with herpes zoster and postherpetic neuralgia (PHN) compared to those without.MethodsUsing the National Health Insurance Research Database (NHIRD), we established a herpes zoster cohort of people diagnosed with herpes zoster between 2004 and 2008 as study cases. Another subset of the NHIRD, which was randomly selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…We found the incidence rate of HZ was 5.54 per 1000 personyears in Taiwan non-AS patients, and 6.52 per 1000 personyears in Taiwan AS patients, in this large population-based study. It was reported that the HZ incidence in Taiwan was 4.04 to 6.24 per 1000 person-years, [11][12][13] which was higher than that in the USA (3.2-3.7 per 1000 person-years) 14 or Europe (3.7 per 1000 personyears). 15 The reason for regional differences in HZ morbidity are still unclear; this may be because of the ethnic distinction and the cultural differences.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found the incidence rate of HZ was 5.54 per 1000 personyears in Taiwan non-AS patients, and 6.52 per 1000 personyears in Taiwan AS patients, in this large population-based study. It was reported that the HZ incidence in Taiwan was 4.04 to 6.24 per 1000 person-years, [11][12][13] which was higher than that in the USA (3.2-3.7 per 1000 person-years) 14 or Europe (3.7 per 1000 personyears). 15 The reason for regional differences in HZ morbidity are still unclear; this may be because of the ethnic distinction and the cultural differences.…”
Section: Discussionmentioning
confidence: 90%
“…It was reported that the HZ incidence in Taiwan was 4.04 to 6.24 per 1000 person‐years, which was higher than that in the USA (3.2‐3.7 per 1000 person‐years) or Europe (3.7 per 1000 person‐years) . The reason for regional differences in HZ morbidity are still unclear; this may be because of the ethnic distinction and the cultural differences .…”
Section: Discussionmentioning
confidence: 99%
“…These studies spanned the years 2000 to 2011 and differed in their objectives, study years, and methodology. The incidence of HZ in the general population between 2000 and 2008 ranged from 4.45 to 6.89 per 1000 person-years and increased over time [12][13][14][15][16]. HZ was more frequent in women than men (5.09 versus 4.71 per 1000 person-years, 5.20 versus 4.72 per 1000 population) [14,17].…”
Section: Hz Age-distribution Incidence and Prevalencementioning
confidence: 99%
“…Seven studies reported HZ incidence in Taiwan and all used the NHIRD [12][13][14][15][16][17][18]. These studies spanned the years 2000 to 2011 and differed in their objectives, study years, and methodology.…”
Section: Hz Age-distribution Incidence and Prevalencementioning
confidence: 99%
“…It is defined as a pain involving a dermatome that is sustained for more than 90 days after acute herpes zoster. 15 Lu et al 16…”
Section: Discussionmentioning
confidence: 99%